A transition towards clean propulsion in shipping : The role of PESTLE drivers and implications for policy - Tsvetkova, Anastasia; Hellström, Magnus; Schwartz, Henry; Rabetino, Rodrigo; Syed, Hammad (Elsevier, 2024)
In the context of the ongoing green transition within the maritime sector, this study seeks to explore the interplay of factors influencing the development of clean propulsion technologies. We identify the drivers underpinning the shift towards cleaner propulsion in maritime operations and outline the implications for the future of such technologies. This research is a result of industry-academia effort to develop a collective vision and strategy for a consortium of companies within propulsion sector. The market drivers are identified as part of a technology roadmapping process following PESTLE framework. Additionally, we employ the MICMAC method to discern dependencies and influences among these drivers. The findings indicate that certain drivers, such as fuel pricing and economic incentives, wield considerable independent influence, whereas others, including green financing, political will, and emission targets, exhibit substantial influence but are interdependent with other variables. Overall, most of the 30 drivers identified in the study both influence and depend on other drivers, creating a complex and uncertain system. This research contributes empirically to a holistic understanding of the intricate interplay among diverse market drivers in the context of clean propulsion in the maritime sector. Theoretically, it unveils the interdependent structure of socio-technical regimes and its implications in terms of “windows of opportunity” for niche development.
Keywords: PESTLE; Propulsion technologies; MICMAC; Clean shipping; fi=Julkisjohtaminen|en=Public Management|; fi=Strateginen johtaminen|en=Strategic Management|